2009
DOI: 10.1182/blood-2008-12-164004
|View full text |Cite
|
Sign up to set email alerts
|

The granulocyte-macrophage colony-stimulating factor receptor: linking its structure to cell signaling and its role in disease

Abstract: Already 20 years have passed since the cloning of the granulocyte-macrophage colony-stimulating factor (GM-CSF) receptor ␣-chain, the first member of the GM-CSF/ interleukin (IL)-3/IL-5 family of hemopoietic cytokine receptors to be molecularly characterized. The intervening 2 decades have uncovered a plethora of biologic functions transduced by the GM-CSF receptor (pleiotropy) and revealed distinct signaling networks that couple the receptor to biologic outcomes. Unlike other hemopoietin receptors, the GM-CSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
218
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(232 citation statements)
references
References 144 publications
5
218
0
3
Order By: Relevance
“…GM-CSF triggers several signaling pathways and transcription factors such as c-Myc, pim-1, CCAAT/enhancer-binding protein alpha, PU.1, and STAT5 (6,21). Our finding that the expression of caSTAT5 abolished the need for GM-CSF indicates a pivotal role for STAT5 in the proliferation and maintenance of the characteristic proinflammatory phenotype of MPI cells.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…GM-CSF triggers several signaling pathways and transcription factors such as c-Myc, pim-1, CCAAT/enhancer-binding protein alpha, PU.1, and STAT5 (6,21). Our finding that the expression of caSTAT5 abolished the need for GM-CSF indicates a pivotal role for STAT5 in the proliferation and maintenance of the characteristic proinflammatory phenotype of MPI cells.…”
Section: Discussionmentioning
confidence: 52%
“…S1A). GM-CSF signaling leads to the induction of several pathways in- cluding the activation of STAT5 (6,21). We found that proliferating MPI cells express activated STAT5, as evidenced by its nuclear localization (Fig.…”
Section: Gm-csf-induced Stat5 Confers Self-renewing Capacity To Mpi Cmentioning
confidence: 86%
“…GM-CSF is produced by many types of cells when stimulated with microbial products or inflammatory cytokines and is also produced by antigen-stimulated T lymphocytes (13). GM-CSF stimulates the proliferation and differentiation of committed progenitors that generate neutrophils, monocytes, macrophages and dendritic cells and also activates differentiated myeloid effector cells such as neutrophils, eosinophils, or monocytes to increase their activity or maturation or prolong their survival (14)(15)(16)(17). Small amounts of GM-CSF produced in the lung are necessary for the maturation of alveolar macrophages, which normally catabolize surplus surfactant in the alveoli.…”
mentioning
confidence: 99%
“…GM-CSF plays a critical role in DC maturation and T-cell proliferation and activation, and increases DC-mediated responses to tumor cells. 70 When used as an adjuvant, it might, however, increase MDSCs in the tumor micro-environment and in blood. This deleterious effect remains, however, controversial and its clinical relevance is doubtful.…”
Section: Dc-cikmentioning
confidence: 99%